2016
DOI: 10.1002/joc.4594
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CMIP3 and CMIP5 projected hydrologic conditions over the Upper Colorado River Basin

Abstract: This work presents updated hydrologic projections for the Upper Colorado River Basin (UCRB) using downscaled (approximately 12 km) General Circulation Model (GCM) output from Coupled Model Intercomparison Project – Phase 5 (CMIP5) with a comparison to CMIP3 GCMs. We use the Soil and Water Assessment Tool model to simulate the impacts of end‐of‐century climate change on the UCRB using 21 CMIP5 and 18 CMIP3 GCMs, collected into one CMIP5 ensemble and one CMIP3 ensemble, respectively. Previous CMIP3 studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…Moreover, the temperature increases more under CMIP5 than under CMIP3 scenarios. Several studies have shown that CMIP5 presents warmer and wetter predictions [19,20]. Meanwhile, the ranges of change in both precipitation and runoff under CMIP5 are much wider than under CMIP3, which indicates that the selected CMIP5 scenarios are more effective in capturing future runoff uncertainties than the selected CMIP3 scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the temperature increases more under CMIP5 than under CMIP3 scenarios. Several studies have shown that CMIP5 presents warmer and wetter predictions [19,20]. Meanwhile, the ranges of change in both precipitation and runoff under CMIP5 are much wider than under CMIP3, which indicates that the selected CMIP5 scenarios are more effective in capturing future runoff uncertainties than the selected CMIP3 scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that, compared to CMIP3, CMIP5 ensemble simulations have substantially improved the statistical representation of daily mean precipitation and temperature [17,18]. However, few studies have compared the impacts of CMIP3 and CMIP5 on the design of the planning and management infrastructure of water resources [19][20][21], especially in China [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate projections suggest that temperatures will rise across the Colorado River basin, although precipitation changes are uncertain (e.g., Seager et al, ; Ayers et al, ). These projected changes, combined with frequent, protracted drought, have enhanced the scientific and management communities’ interest in understanding the ways in which major river systems like the Colorado River respond to climatic fluctuations, particularly those that are not uniform across the basin (see Woodhouse et al, ), such as elevation‐dependent warming (Mountain Research Initiative EDW Working Group, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, increases in the number of highelevation stations in the UCRB may have led to an underestimation of elevationdependent warming, particularly during the spring. This phenomenon is unlikely limited to this specific basin and may be present in other high-elevation watersheds across the western United States K E Y W O R D S climate trends, Colorado River, elevation-dependent warming, gridded data, temperature 1 | INTRODUCTION Climate projections suggest that temperatures will rise across the Colorado River basin, although precipitation changes are uncertain (e.g., Seager et al, 2013;Ayers et al, 2016). These projected changes, combined with frequent, protracted drought, have enhanced the scientific and management communities' interest in understanding the ways in which major river systems like the Colorado River respond to climatic fluctuations, particularly those that are not uniform across the basin (see Woodhouse et al, 2016), such as elevation-dependent warming (Mountain Research Initiative EDW Working Group, 2015).…”
mentioning
confidence: 99%